Single source dual energy CT: What is the optimal monochromatic energy level for the analysis of the lung parenchyma?. Issue 88 (March 2017) - Ohana, M.; Labani, A.; Severac, F.; Jeung, M.Y.; Gaertner, S.; Caspar, T.; Roy, C.
Graphical abstract: Highlights: Lung parenchyma aspect varies with the monochromatic energy level in spectral CT. Optimal diagnostic and image quality is obtained at 50–55 keV. Mediastinum and parenchyma could be read on the same monochromatic energy level. Abstract: Objective: To determine the optimal monochromatic energy level for lung parenchyma analysis in spectral CT. Methods: All 50 examinations (58% men, 64.8 ± 16yo) from an IRB-approved prospective study on single-source dual energy chest CT were retrospectively included and analyzed. Monochromatic images in lung window reconstructed every 5 keV from 40 to 140 keV were independently assessed by two chest radiologists. Based on the overall image quality and the depiction/conspicuity of parenchymal lesions, each reader had to designate for every patient the keV level providing the best diagnostic and image quality. Results: 72% of the examinations exhibited parenchymal lesions. Reader 1 picked the 55 keV monochromatic reconstruction in 52% of cases, 50 in 30% and 60 in 18%. Reader 2 chose 50 keV in 52% cases, 55 in 40%, 60 in 6% and 40 in 2%. The 50 and 55 keV levels were chosen by at least one reader in 64% and 76% of all patients, respectively. Merging 50 and 55 keV into one category results in an optimal setting selected by reader 1 in 82% of patients and by reader 2 in 92%, with a 74% concomitant agreement. Conclusion: The best image quality for lung parenchyma in spectral CT is obtained with the 50–55 keV monochromatic reconstructions.